Searching for new early detection markers of oral epithelial dysplasia and oral squamous cell carcinoma using oral liquid-based cytology - Akimori, Toshiyuki; Yamazaki, Manabu; Abé, Tatsuya; Maruyama, Satoshi; Tomihara, Kei; Maeda, Takeyasu; Tanuma, Jun-ichi (Journal of oral and maxillofacial surgery, medicine, and pathology, 2024)
Oral squamous cell carcinomas (SCCs) arise from oral potentially malignant disorders (OPMDs), including oral epithelial dysplasia (OED); however, useful detections markers for early detection of OED and oral SCC are lacking. In this study, we aimed to evaluate the sequential mRNA and protein expression patterns of BRD4, c-MYC, TP53, and MUC21 in human oral samples by liquid-based cytology (LBC) and determine whether these markers are useful for early detection of OED and oral SCC when combined with oral cytological screening. A total 200 patients were obtained from our hospital between 2020 and 2022. These are samples from same cases with oral cytology and corresponding histological diagnosis. The expression of these markers was examined by immunocytochemistry and mRNA analysis. The percentages of cells with nuclear or cytoplasmic immunostaining were calculated using the labeling index (LI). BRD4, c-MYC, and TP53 mRNA expression levels were upregulated in tissue during progression from a status of negative for intraepithelial lesions or malignancy (NILM) to positive for SCC. BRD4-LI and c-MYC-LI significantly increased in low-grade squamous intraepithelial lesions (LSIL), high-grade squamous intraepithelial lesions (HSIL) and SCC samples, whereas the expression of MUC21 mRNA and MUC21-LI gradually decreased. TP53-LI increased only in SCC samples. We conclude that monitoring BRD4 and c-MYC expression with immunocytochemistry could improve the early detection of OED and oral SCC.